2007
DOI: 10.1371/journal.pone.0001027
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Dependence of Inbreeding Depression in a Wild Bird Population

Abstract: BackgroundInbreeding depression occurs when the offspring produced as a result of matings between relatives show reduced fitness, and is generally understood as a consequence of the elevated expression of deleterious recessive alleles. How inbreeding depression varies across environments is of importance for the evolution of inbreeding avoidance behaviour, and for understanding extinction risks in small populations. However, inbreeding-by-environment (I×E) interactions have rarely been investigated in wild pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
3
34
2
1
Order By: Relevance
“…a general pattern of increased inbreeding depression under more stressful environments (Fox & Reed 2011;Marr et al 2006;Szulkin & Sheldon 2007). Our results provide some evidence that the stress imposed by a change in social environment (the discontinuation of helper provisioning for post-independence meerkats) is analogous to the ecologically stressful environments reported in other animal populations.…”
Section: Previous Investigations Of Environmental Effects On Inbreedisupporting
confidence: 61%
See 2 more Smart Citations
“…a general pattern of increased inbreeding depression under more stressful environments (Fox & Reed 2011;Marr et al 2006;Szulkin & Sheldon 2007). Our results provide some evidence that the stress imposed by a change in social environment (the discontinuation of helper provisioning for post-independence meerkats) is analogous to the ecologically stressful environments reported in other animal populations.…”
Section: Previous Investigations Of Environmental Effects On Inbreedisupporting
confidence: 61%
“…Keller & Waller 2002;Richardson et al 2004;RiouxPaquette et al 2010;Schiegg et al 2006;Szulkin & Sheldon 2007;Walling et al 2011).…”
Section: Occurrence Of Inbreedingunclassified
See 1 more Smart Citation
“…Several studies have found that the association between genetic diversity (or inbreeding) and different components of fitness become stronger under stressful conditions (Armbruster & Reed, 2005; Fox & Reed, 2011), but most evidence on this respect comes from experimental approaches and only a few studies have analyzed such interactions in wild populations (Forcada & Hoffman, 2014; Marr et al., 2006; Szulkin & Sheldon, 2007). Here, we quantified the relationship between heterozygosity and fitness along an environmental continuum, comprising harsh (wet–cool) and benign (dry–warm) years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when comparing with other studies that use this approach, hihi have a moderate to high genetic load (e.g. song sparrow (M. melodia), Keller 1998; collared flycatcher (Ficedula albicollis), Kruuk et al 2002;Darwin finches, Keller et al 2002; great tit (Parus major), Szulkin & Sheldon 2007) and is also higher than most estimates reported for laboratory populations, and lower than those reported for zoo populations (for reviews see Lynch & Walsh 1998;Keller 1998).…”
Section: Discussionmentioning
confidence: 99%